Efektifitas Aplikasi Tepung Asap Pada Bakso Dengan Sistem Pengawetan Mikroenkapsulasi Asap Cair - Fouk, Petronela; Abrina Anggraini, Sinar Perbawani; Yuniningsih, Susy (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
Coconut shell is an alternative type of raw material that can be used as a base for making liquid smoke because it contains cellulose, lignin, hemicellulose, and ash. Liquid smoke is a natural preservative that is obtained from the results of smoke condensate in the pyrolysis process of wood content containing hemicellulose, cellulose, and lignin. The use of liquid smoke is not only in the form of liquids because in the form of liquids, but phenol components and organic acids will also evaporate if stored for a long time so that it requires special containers and places for storing liquid smoke, so the development of microencapsulation technology is needed to cover phenolic compounds and starch acid using maltodextrin. Previous researchers stated that smoked flour had 70.79% phenolic compounds and 11.10% acetic acid, while the phenol compounds in liquid smoke were 24.03% and 57.70% acetic acid. The purpose of this study was to determine the acidity level of the meatballs with a liquid smoke microencapsulation system. The drying temperatures in the microencapsulation process were (ºC) 135, 140, 145, and 150 with a maltodextrin concentration of 30% and a particle size of 120 mesh. The results of the analysis of the acidity levels in meatballs increased at 145 ºC because there was an exponential bacterial growth phase, while at temperatures of 140 ºC and 145 ºC there was a stationary phase where bacterial growth was constant and at 150 ºC the acidity level decreased due to the increase in temperature. affect the speed of cell division so that acidity levels begin to decrease or be exhausted